2020
DOI: 10.1155/2020/9867595
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Inhibitor, Brusatol in Combination with Trastuzumab Exerts Synergistic Antitumor Activity in HER2-Positive Cancers by Inhibiting Nrf2/HO-1 and HER2-AKT/ERK1/2 Pathways

Abstract: The HER2-targeting antibody trastuzumab has shown effectiveness in treating HER2-positive breast and gastric cancers; however, its responses are limited. Currently, Nrf2 has been deemed as a key transcription factor in promoting cancer progression and resistance by crosstalk with other proliferative signaling pathways. Brusatol as a novel Nrf2 inhibitor has been deemed as an efficacious and safe drug candidate in cancer therapy. In this study, we firstly reported that brusatol exerted the growth-inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 51 publications
(66 reference statements)
0
37
0
Order By: Relevance
“…Pharmacological inhibition of Nrf2 using trigonelline sensitized pancreatic cells to apoptosis [ 82 ]. Synergistic anti-cancer effects of brusatol and trastuzumab (HER2 targeting agent) were reported in HER2 positive BC and associated with induction of reactive oxygen species (ROS) production and apoptosis [ 83 ]. Furthermore, cooperative effects of brusatol and other anticancer agents, including gemcitabine (in pancreatic carcinomas) [ 84 ], cytarabine (Ara-C) (in acute myeloid leukemia) [ 85 ], luteolin (in gastric cancers) [ 86 ], and paclitaxel (in BCs) [ 87 , 88 ], were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of Nrf2 using trigonelline sensitized pancreatic cells to apoptosis [ 82 ]. Synergistic anti-cancer effects of brusatol and trastuzumab (HER2 targeting agent) were reported in HER2 positive BC and associated with induction of reactive oxygen species (ROS) production and apoptosis [ 83 ]. Furthermore, cooperative effects of brusatol and other anticancer agents, including gemcitabine (in pancreatic carcinomas) [ 84 ], cytarabine (Ara-C) (in acute myeloid leukemia) [ 85 ], luteolin (in gastric cancers) [ 86 ], and paclitaxel (in BCs) [ 87 , 88 ], were observed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xiang et al reported that brusatol abrogate gemcitabine-induced NRF2 activation in pancreatic cancer cells and potentiates gemcitabine-induced cell growth inhibition in vitro and xenograft tumor growth inhibition in vivo with reduced NRF2 expression in brusatol-treated xenograft tumors [ 108 ]; Yang, et al reported that brusatol synergistically enhanced the antitumor activity of trastuzumab against HER2-positive cancer cells [ 109 ]; trastuzumab markedly enhanced brusatol-induced ROS accumulation and apoptosis level [ 109 ]. The authors stated that the study is a new insight on exploring NRF2 inhibition in combination with HER2-targeted trastuzumab as a potential clinical treatment regimen for treating HER2-positive cancers [ 109 ]; Very recently, Xie, et al reported that in lung cancer cells, brusatol significantly suppressed the expression of NRF2 and HO-1 (a NRF2 downstream target), and abrogated tBHQ-induced NRF2 activation [ 110 ]; brusatol suppressed the expression level of Bcl-2 and Bcl-xl, accentuated Bax and Bak, increased cleaved caspases-3/8, and cleaved PARP but upregulated XIAP [ 110 ]. These authors proposed that brusatol action may involve the modulation of ROS-mediated mitochondrial-dependent pathway and inhibition of NRF2-mediated antioxidant response [ 110 ].…”
Section: Nrf2mentioning
confidence: 99%
“…As a natural quassinoid, brusatol is known to stimulate the polyubiquitination of NRF2 and inhibit NRF2 signaling [ 65 ] ( Figure 1 ). Studies suggest its usage as an antineoplastic drug and chemotherapeutic adjuvant [ 66 , 67 ]. However, brusatol causes various cardiovascular side effects and may lead to serious neurologic and organ damage by reversing the therapeutic effects of other drugs.…”
Section: Nddss In the Delivery Of Nrf2 Modulators For Cancer Therapymentioning
confidence: 99%